CHUICHAI NANGMANEE : PERFORMANCE TECHNIQUE OF BOONNAK THANTARANON - Pungpo, Kanthida; Chantamala, Ourarom (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
This research aims to 1) to study the history and works in the field of broadcast performance and the important role of Ajarn Boonnak Thantaranon to study the dance techniques and the Lakorn Nork, the story of Kaew Nama, the Chuichai Nangmanee series by Ajarn Boonnak Thantaranon, from research papers and field data. The sample group included2 people of experts in Thai dance, a group of 5 students who received the role of a dance drama from Ajarn Boonnak Thantaranon, a group of 5 practitioners and 10 general informants, in a total of 22 people. Tools used in the research consists of structured and unstructured surveys, observations, and interviews. Then present the research results by descriptive analysis. The results showed that 1) Ajarn Boonnak Thantaranon is an artist who specializes in Thai dance, gifted with theatrical arts. When the experience has been accumulated to become the identity of the performance, it is a unique trick of himself. He is an artist who has a beautiful dancing style. He is also the one who preserves and inherits the ancient dance movements until the present 2) Ajarn Boonnak Thantaranon invented the dance moves that show off the beauty of Nangmanee. There will be a dance style that is different from other Chuichai sets, more than showing off and showing satisfaction that can transform body transfigure beautifully. There was also the idea of inventing gestures to mimic the horse gesture, mixed into the show by striking the chorus in the beautiful Thai dance postures.